Preparation of Financial Statements Based on SAK-EMKM in Micro, Small and Medium Enterprises (UMKM) Ekky Store in North Toraja Regency - Tambing, Inggrid; Kawulur, Arie F.; Kantohe, Meidy (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study aims to examine the preparation of financial statements based on SAK-EMKM in Micro, Small and Medium Enterprises (UMKM) of Toko Ekky in North Toraja Regency. The focus of this research is the understanding of UMKM owners regarding the preparation of financial statements, the obstacles faced in compiling financial statements, and how to prepare financial statements based on SAK-EMKM in Toko Ekky UMKM. This study uses a qualitative method with a case study approach. Data was collected through interviews, observations, and documentation. The results of the study show that the owner of Toko Ekky UMKM has not understood the preparation of financial statements in accordance with SAK-EMKM. The obstacles faced are the lack of knowledge and understanding of accounting and the limitations of human resources. In compiling financial statements, Toko Ekky UMKM only make simple records related to cash receipts and expenditures. Therefore, assistance and training are needed for MSME owners to be able to prepare financial statements in accordance with SAK-EMKM to improve better financial management.